Diabetes mellitus and Parkinson disease. (8th May 2018) - Pagano, Gennaro; Polychronis, Sotirios; Wilson, Heather; Giordano, Beniamino; Ferrara, Nicola; Niccolini, Flavia; Politis, Marios
Abstract : Objective: To investigate whether diabetes mellitus is associated with Parkinson-like pathology in people without Parkinson disease and to evaluate the effect of diabetes mellitus on markers of Parkinson pathology and clinical progression in drug-naive patients with early-stage Parkinson disease. Methods: We compared 25 patients with Parkinson disease and diabetes mellitus to 25 without diabetes mellitus, and 14 patients with diabetes mellitus and no Parkinson disease to 14 healthy controls (people with no diabetes mellitus or Parkinson disease). The clinical diagnosis of diabetes mellitus was confirmed by 2 consecutive fasting measurements of serum glucose levels >126 mL/dL. Over a 36-month follow-up period, we then investigated in the population with Parkinson disease whether the presence of diabetes mellitus was associated with faster motor progression or cognitive decline. Results: The presence of diabetes mellitus was associated with higher motor scores ( p < 0.01), lower striatal dopamine transporter binding ( p < 0.05), and higher tau CSF levels ( p < 0.05) in patients with Parkinson disease. In patients with diabetes but without Parkinson disease, the presence of diabetes mellitus was associated with lower striatal dopamine transporter binding ( p < 0.05) and higher tau ( p < 0.05) and α-synuclein ( p < 0.05) CSF levels compared to healthy controls. At the Cox survival analysis in the population of patients with Parkinson disease, the presence of diabetes mellitus was associated with faster motor progression (hazard ratio = 4.521, 95% confidence interval = 1.468–13.926; p < 0.01) and cognitive decline (hazard ratio = 9.314, 95% confidence interval = 1.164–74.519; p < 0.05). Conclusions: Diabetes mellitus may predispose toward a Parkinson-like pathology, and when present in patients with Parkinson disease, can induce a more aggressive phenotype.